Pelatihan Penerapan Teknologi Pembuatan Pakan Organik Untuk Pencegahan Penyakit Pada Udang Windu Di Desa Tamangapa Kecamatan Ma’rang Kabupaten Pangkep - Harlina; Syahrul; Hamdillah, Andi; Kamaruddin (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
The main problem faced by tiger prawn shrimp farmers is the high mortality rate in ponds due to diseases such as Vibrios sp. The common method for preventing and controlling vibriosis is still relying on chemicals and antibiotics. The use of continuous and uncontrolled chemicals and antibiotics have some negative impacts on bacterial resistance, residue and pollute the shrimp farming. To prevent the negative side from antibiotic, natural product has become one of other alternative as antimicrobial. This community service aims to provide knowledge and skills to shrimp farmer groups through training and mentoring so that they are able to independently make organic shrimp feed made from local raw materials, easy to obtain, inexpensive and can be used in disease prevention in tiger shrimp farming. The method used was a participatory method. It involves as many partners as possible participation in lectures, discussions, and practice of making feed. The result of this activity was an increase in knowledge and skills in the application of organic feed manufacturing technology based on the results of questions and answers, discussions. In addition, tiger shrimp farmer groups were very enthusiastic in the training. They also were optimistic in producing organic feed.